VICTIMS OF ATTACKS WITH EDGED AND BLUNT WEAPONS: THE PICTURE DRAWN BY DEMAND AT AN EMERGENCY UNIT - Júlio César Batista Santana; Bianca Santana Dutra; Juliana Alves Viana; Lidiane Sales Vieira; Cecília Maria Lima Cardoso (Universidade Federal do Paraná, 2012)
This study aimed to establish from care records the epidemiological characteristics of 105 victims of edged/blunt weapon attacks who were attended by an ambulance unit in a town in the state of Minas Gerais, in the period 2006 - 2008. The victims were predominantly men, aged between 21 and 40 years; the majority of wounds were to the head and neck and the limbs and thorax, and were due to the use of knives; the events took place mainly at weekends. The majority of victims were taken to a Center of Excellence hospital, although in 5.72% of cases the victim was declared dead at the scene. The results show the necessity of implementing public health policies directed at preventing, controlling and minimizing these offences.